THE EFFECT OF INCUBATION TIME AND DOSE OF CHICKEN MANURE COMPOST ON THE GROWTH AND YIELD OF PAKCOY (Brassica rapa L.) - Lake, Yoneta; Neonbeni , Eduardus Yosef; Bria, Deseriana; Naisali , Hyldegardis (Universitas Veteran Bangun Nusantara, 2025)
Pakcoy has high economic value, therefore it is necessary to increase pakcoy production. To overcome the problems that arise in pakcoy cultivation, it is necessary to carry out proper cultivation that is enviromentally friendly. This study aims to determine the effect of incubation time and the dosageof chicken manure compost onthe growth of pakcoy (Brasia rapa L.) plants. This study was conducted from October to December 2023, behind the Timor University Library Building and the results of the study were analyzed in the Laboratory of the Faculty of Agriculture, Science and Health, Timor University. This study used a factorial Completely Randomized Design (CRD) consisting of 2 factors. The first factor is the incubation period (W) which consists of four levels, namely the first level (Without), (7 days), (14 days) and (21 days). The second factor is the dose of chicken manure compost (T) which consists of 3 levels, namely (Without), (35 g/polybag), (50 g/polybag). There are 12 treatment combinations that are repeated 3 times to obtain 36 experimental units. The observed observation parameters include plant height, number of leaves, fresh plant weight, root length, fresh root weight, dry plant weight, dry root weight, harvest index. The data collected was analyzed using 2-factor Completely Randomized Design (CRD) analysis of variance (Anova). Next, the treatment average was tested further using the Duncan Multiple Range Test (DMRT) with a significance of 5% according to instructions (Gomes and Gomes, 2010). Data analysis using the SAS 9.1 program. The results of the study showed that there was an interaction between the treatment factors of incubation period and the dose of chicken manure compost on the observation of the number of leaves 7 HST. Keywords: Chicken manure, compost dosage, incubation time, pakcoy plants